Tindak Pidana Pencurian Jaringan Wifi Menurut Pasal 30 Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - M. Syuib; Maisarah Maisarah (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
This research is motivated by the number of internet (Wi-Fi) stealing around Syiah Kuala Sub District, Banda Aceh, in which this action can disserve the owner of the internet and against to the law. The method of this research is qualitative in which it describes the result of research objectively to conditions encountered in the gorund. The research problems are how the Wi-Fi internet is theft (modus operandi) and what are juridical consequences of the act according to Article 30 of Law No. 19/2016 concerning Electronic Information and Transactions, and how is the Islamic law perspective on the act of internet stealing. The result showed that the modus operandi of Wi-Fi internet stealing is by using a laptop or mobile phone and downloading certain software or applications they need to break through the security system and obtain a username and password. Theft or internet (Wi-Fi) stealing in Syiah Kuala District, Banda Aceh City, can be punished under Article 30 paragraph (1), (2) and (3) in conjunction with Article 46 paragraph (1), (2) and (3) Law No. 19/2016 concerning Electronic Information and Transactions. The action categorized as illegal access. The theft of the Wi-Fi internet in Islamic law perspective is clearly prohibited (haram) due to someone has used other people property without permission. So, it is expected that the perpetrators or other people in order not to do the actin because it is against to the law, and also expected the Wi-Fi owner could report the case to the police.